Probiotics for prevention of necrotizing enterocolitis—where do we stand in 2017? - Robinson, Joan L. (Journal of Laboratory and Precision Medicine, 2017)
Necrotizing enterocolitis (NEC) affects primarily preterm infants and can lead to the devastating outcomes of intestinal failure secondary to resection of extensive necrotic bowel or death. A disordered intestinal microbiome is thought to be a risk factor for NEC. Probiotics are live microorganisms administered as food supplements or as pharmaceuticals in an attempt to improve human health. If the intestine of a preterm infant could be deliberately colonized with non-pathogenic organisms administered as a probiotic, the risk of NEC may decrease (1).